ANALISIS BEBAN KERJA PADA RECEPTIONIST SELAMA HIGH SEASON PACIFIC PALACE HOTEL BATAM - Prisila Natacia Suciadi; Okki Kurnia; Devid Trinaldo Simatupang; Nensi Lapotulo (Bajang Institute, 2024)
During high season, hotels often experience high occupancy rates, which can lead to increased workload for hotel staff, including receptionists, housekeeping, and other services (Alrawabdeh, 2022). Receptionists play an important role as the spearhead in providing services to guests, from the check-in process, answering guest questions, to handling complaints. High workloads during high season often lead to decreased performance, work stress, and even potential errors in service (Sáez-Fernández, 2020). Based on the description above, researchers are interested in conducting a study entitled